The answer is A bcs y=mx +c
Answer/Step-by-step explanation:
Given:
m<EFH = (5x + 1)°
m<HFG = 62°
m<EFG = (18x + 11)°
Required:
1. Value of x
2. m<EFH
3. m<EFG
SOLUTION:
1. Value of x
m<EFH + m<HFG = m<EFG (angle addition postulate)
(5x + 1) + 62 = (18x + 11)
Solve for x using this equation
5x + 1 + 62 = 18x + 11
5x + 63 = 18x + 11
Subtract 18x from both sides
5x + 63 - 18x = 18x + 11 - 18x
-13x + 63 = 11
Subtract 63 from both sides
-13x + 63 - 63 = 11 - 63
-13x = -52
Divide both sides by -13
-13x/-13 = -52/-13
x = 4
2. m<EFH = 5x + 1
Plug in the value of x
m<EFH = 5(4) + 1 = 20 + 1 = 21°
3. m<EFG = 18x + 11
m<EFG = 18(4) + 11 = 72 + 11 = 83°
The answer is: ![13-\frac{2}{9}g](https://tex.z-dn.net/?f=13-%5Cfrac%7B2%7D%7B9%7Dg)
The explanation is shown below:
1- You have the following expression given in the exercise:
![(\frac{30}{45}g+20)-(\frac{8}{9}g+7)](https://tex.z-dn.net/?f=%28%5Cfrac%7B30%7D%7B45%7Dg%2B20%29-%28%5Cfrac%7B8%7D%7B9%7Dg%2B7%29)
2- When you multiply signs, you obtain:
![\frac{30}{45}g+20-\frac{8}{9}g-7](https://tex.z-dn.net/?f=%5Cfrac%7B30%7D%7B45%7Dg%2B20-%5Cfrac%7B8%7D%7B9%7Dg-7)
3. Now, you must add like terms, as following:
![-\frac{2}{9}g+13](https://tex.z-dn.net/?f=-%5Cfrac%7B2%7D%7B9%7Dg%2B13)
4. Therefore, you have that the expression simplified is:
![13-\frac{2}{9}g](https://tex.z-dn.net/?f=13-%5Cfrac%7B2%7D%7B9%7Dg)